Pengaruh Keragaman Produk, Harga Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Brandan Donuts Di Pangkalan Berandan - Muhammad Tulus Pekerti; Erni Junaida; Rahmi Meutia (Universitas Labuhanbatu, 2023)
This study aims to determine the effect of product diversity and price on consumer satisfaction of Brandan Donuts in Pangkalan Berandan. This study used a sample of 96 respondents with a minimum purchase frequency of two or more times. The method of analysis used multiple linear regression, t test, F test and coefficient of determination test. The results of this study show Y = 5.484 + 0.612X1 + 0.313X2. The results of the t test show that the product diversity factor has a significant effect on consumer satisfaction of Brandan Donuts in Pangkalan Berandan, price has a significant effect on consumer satisfaction of Brandan Donuts in Pangkalan Berandan. The results of the coefficient of determination test (adjusted R2) obtained a value of 0.556 or 55.6%, this means that product diversity and price variables affect Brandan Donuts consumer satisfaction in Pangkalan Berandan. While the remaining 44.4% is influenced by other variables not examined in this study.